Respuesta :
Answer:
Distribute
Step-by-step explanation:
You will want to distribute 3 by 3x and -5x, Which will then make your equation
9x-15x+2=-8
You are using pemdas in this equation so there for you distribute first .
Example : 3(3x-5x)+2=-8
You will multiply
3 (3x-5x)
9x -15 x +2=-8
Then add and subtract with same variables
-6x = -6
Then you divide by -6
X=1
Example : 3(3x-5x)+2=-8
You will multiply
3 (3x-5x)
9x -15 x +2=-8
Then add and subtract with same variables
-6x = -6
Then you divide by -6
X=1